Demographic consequences of mutualism disruption: Browsing and big‐headed ant invasion drive acacia population declines. Issue 5 (21st March 2022) - Hays, Brandon R.; Riginos, Corinna; Palmer, Todd M.; Doak, Daniel F.; Gituku, Benard C.; Maiyo, Nelly J.; Mutisya, Samuel; Musila, Simon; Goheen, Jacob R.
Abstract: Across the globe, biological invasions have disrupted mutualisms, producing reverberating consequences for ecosystems. Although invasive species frequently trigger mutualism disruptions, few studies have quantified the demographic mechanisms by which mutualism breakdown may generate population effects. In a Kenyan savanna, the invasive big‐headed ant ( Pheidole megacephala ) has disrupted a foundational mutualism between the monodominant whistling‐thorn tree ( Acacia drepanolobium ) and native ants ( Crematogaster spp.) that deter browsing by large mammalian herbivores. We conducted experiments to quantify the demographic consequences of this mutualism disruption in the presence and absence of large mammalian herbivores. Invasion by P. megacephala exacerbated population declines of A. drepanolobium, primarily through decreased survival and reproduction of adult trees. However, these fitness reductions were small compared to those resulting from the presence of large mammalian herbivores, which negatively impacted growth and survival. Contrary to expectation, the expulsion of metabolically costly Crematogaster mutualists by P. megacephala did not result in higher population growth rates for trees protected from large mammalian herbivores. Our results suggest that invasive P. megacephala may impose a direct metabolic cost to trees exceeding that of native mutualists while providing no protection from browsing by large mammalian herbivores. Across landscapes, we expect that invasion by P. megacephala will reduce A. drepanolobium populations, but that the magnitude and demographic pathways of this effect will hinge on the presence and abundance of browsers.